The Influence of Using social media on Students' Attitudes in Carrying Out Bullying from a Diversity Perspective: Case Study of Class IX SMP Negeri 35 Percut Sei Tuan - Yosua Gabe Maruli Sianggaran; Parlaungan Gabriel Siahaan; Novridah Reanti Purba; Shelly Elprida Gajahmanik; Taslima Amelia Taufik (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to find out the impact of the use of Social Media that has influenced students towards bullying and to find out the extent of students' understanding in respecting differences and diversity so that bullying does not occur. this research uses descriptive methods by conducting interviews with respondents of one class of students of SMP Negeri 35 Medan. The results of the research conducted are that these students already have a good attitude in using social media and students also understand how to respect diversity and not commit acts of bullying on social media